Significance of record keeping. - Ishak, Rosbi (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2024)
Maintaining financial records is crucial not just for individuals and companies, but it also significantly impacts the broader economic framework. Transparency and accountability in financial management allows all parties involved, including shareholders, employees and customers, to understand and the company's financial situation. This not only increases trust but also promotes a culture of integrity in the organization. With clear records, any disputes or issues that arise can be resolved more easily. Financial Planning and Analysis; Well-structured financial records facilitate the examination of financial trends across different periods. Through this analysis, business proprietors can discern patterns that may enhance profitability. Furthermore, this insight enables more precise forecasting, which is instrumental in making informed strategic choices, including potential investments or cost-cutting measures. Tax Compliance; Maintaining accurate records is essential not only for filing tax returns but also for supplying proof during a tax authority audit. By retaining all receipts and relevant documentation, both individuals and businesses can minimize the likelihood of incurring penalties and fines due to non compliance.